PENGARUH PERCEIVED VALUE TERHADAP KEPUTUSAN PEMBELIAN EMAS 22% DI KOTA KRAKSAAN KABUPATEN PROBOLINGGO (Studi Pada Toko Pusaka Mas) - Ibnu Hajar Dewantara (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to analyze the influence of perceived value on purchasing decisions gold 22% Kraksaan city probolinggo. To find out how much influence the dependent variable (buying decisions) to the independent variables (Quality/Performance Value, Emotional Value, Functional Value, Social Value). This study uses multiple regression analysis with SPSS version 17.0. This data collection method uses a questionnaire to consumer of Pusaka Mas store in Kraksaan.. Questionnaires were distributed 100 questionnaires. The results of studies using multiple linear regression analysis, showed that simultaneous variabel quality/performance value (X1), emotional value (X2), functional value (X3), social value (X4), has a significant influence on buying decisions (Y). While partial, variable funtcional value showed a significant effect on decision buying consumen. Keywords: Perceived Value, Quality/Performance Value, Emotional Value, Functional Value, Social Value, and Purchase Decision.